Child tuberculosis in Respira Lung Hospital, Yogyakarta: demographic and clinical profiles - Stefani Candra Firmanti; Rina Triasih (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Tuberculosis (TB) remains a significant source of morbidity and mortality among children in endemic settings. Demografic and clinical profiles of children with TB in Yogyakarta have not been well documented. A total of 80 children with TB were diagnosed with TB during the study period. There were 41 (51.2%) females and 39 (48.8%) males. The case findings of child TB cases has been increasing from 20 cases in 2014, 28 cases in 2015, and 32 cases in 2016. The majority of the children (89.3%) aged less than 5 years. The most common symptoms were cough 50 (62.5%), followed by weight loss 45 (56.3%), and fever 28 (35%). Contact with a TB case was identified in 46 (57.5%) children. Mantoux test was done in 76 (95%) children with positive result documented in 61(76.3%) children. Chest X-ray was done in 54 (67.5%) children, of which 52 (65%) chest X- rays showed suggestive of TB. Confirmed diagnosis (bacteriology) was only documented in one child (1.25%).